Análise da eficiência no setor varejista de gêneros alimentícios - Sonza, Igor Bernardi (2007)
The concentration process restricted the Market Share of the retail sector of foodstuffs in a few companies, that have withhold a big part of the reserves. In accordance with ABRAS (2006), there is a large disparity among the participation of each format, the number of stores and the reserves of the foodstuffs retailing sector. In attention of this fact, it is perceptive that, in absolute terms, the hypermarkets possess advantage in relation to the supermarkets and the small markets, but not necessarily this logic is true in relative terms. Through the analysis of the DEA (Data Envelopment Analysis) it is possible to attribute weights to the variables considered and to determine the efficiency of the companies, thus identifying this relation. According to this point of view, the study in question aims at carrying through a comparative analysis between the size and the efficiency of the biggest foodstuffs retailing companies of Brazil through the DEA calculation, and to identify alternative targets for the less efficient companies. In the Kruskal-Wallis test, the null hypotheses of differences between size and efficiency was rejected, that is, it was found that the means are significantly different for the three groups (small, medium and large companies). Through the differences among means, it was also found that the large companies are more efficient, and that the medium companies possess advantage in terms of efficiency in relation to the small ones, with the exception of the analyses BCC and Superefficiency of model BCC, that had identified superiority of the small companies in relation to the medium ones.